Small and medium-sized enterprises in international economic law - Rensmann, Thilo (Oxford : Oxford University Press, 2017)
Examining the effect widening access to the global marketplace has had on the international legal landscape, this book presents the first comprehensive analysis of the interaction between small and medium-sized enterprises (SMEs) and international economic law.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 5, 2017).
Keywords: International economic relations -- Law and legislation; Small business -- Finance -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law